Assessing Implementation Integrity of a National Nutrition Education Program: A Case Study of Share Our Strength's Operation Frontline - Chris L. S. Coryn; Daniela C. Schröter; Anne Cullen; Laura Semen; Janet McLaughlin (Journal of MultiDisciplinary Evaluation)
Background: Treatment implementation is not just one thing but rather is a multifaceted process that includes treatment delivery, treatment receipt, and treatment adherence. As such, local variations in implementation and service delivery of interventions are an inevitable.